Barriers and facilitators to influenza vaccination observed by officers of national immunization programs in South America countries with contrasting coverage rates - Miguel Ángel González-Block; Sandra Patricia Díaz Portillo; Juan Arroyo Laguna; Yamila Comes; Pedro Crocco; Andréa Fachel-Leal; Laura Noboa; Daniela Riva Knauth; Berenice Rodríguez-Zea; Mónica Ruoti; Elsa Sarti; Esteban Puentes (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2022)
Influenza is a severe, vaccine-preventable disease. Vaccination programs across Latin American countries show contrasting coverage rates, from 29% in Paraguay to 89% in Brazil. This study explores how national influenza vaccination programs in the chosen South American countries address vaccine confidence and convenience, as well as complacency toward the disease. Barriers and facilitators to influenza vaccination programs in their relation to vaccine hesitancy were observed by documentary analysis and interviews with 38 national immunization program officers in high- (Brazil and Chile) and low-performing (Paraguay, Peru, and Uruguay) countries. Influenza vaccination policies, financing, purchasing, coordination, and accessibility are considered good or acceptable. National communication strategies focus on vaccine availability during campaigns. In Chile, Paraguay, and Uruguay, anti-vaccine propaganda was mentioned as a problem. Programming and implementation face human resource shortages across most countries. Statistical information, health information systems, and nominal risk-group records are available, with limitations in Peru and Paraguay. Health promotion, supervision, monitoring, and evaluation are perceived as opportunities to address confidence and complacency. Influenza vaccination programs identify and act on most barriers and facilitators affecting influenza vaccine hesitancy via supply-side strategies which mostly address vaccine convenience. Confidence and complacency are insufficiently addressed, except for Uruguay. Programs have the opportunity to develop integral supply and demand-side approaches.